RESTRUKTURISASI PEMBIAYAAN MURABAHAH: Analisis Yuridis Peraturan Bank Indonesia - Moh. Asra; Wilda Al-Hanun; Arif Hariyanto (LP2M Universitas Ibrahimy, 2018)
This study examines how the restructuring process occurred in the financing of murabahah problems both in Islamic banking and in other sharia business units. The problematic financing case occurs suddenly, because in general before experiencing a problematic phase, at this stage the bank will warn customers in a familial manner. Basically, the implementation of the Murabahah Restructuring is carried out with the principle of prudence and sharia principles through the rescheduling process, re-requirements, and rearrangement. In general, how this restructuring process must be in accordance with Bank Indonesia Regulation number No. 10/18/ PBI/2008 as amended by Bank Indonesia Regulation Number 13/9PBI/2011 concerning financing restructuring for Islamic banks and Islamic business units.